Simple model to simulate OCT-depth signal in weakly and strongly scattering homogeneous media. (28th October 2016) - Varkentin, Arthur; Otte, Maya; Meinhardt-Wollweber, Merve; Rahlves, Maik; Mazurenka, Mikhail; Morgner, Uwe; Roth, Bernhard
Abstract: We present a simple and efficient Monte Carlo model to predict the scattering coefficients and the influence of multiple photon scattering with increasing concentration of scattering centers from optical coherence tomography (OCT) data. While the model reliably estimates optical sample parameters for a broad range of concentrations, it does not require inclusion of more complex phenomena such as dependent scattering. Instead, it relies on a particular weighting function which is introduced to describe various orders of multiple scattering events. In weakly scattering homogeneous media the measured scattering coefficient μ s depends linearly on the concentration of scattering centers. In the case of strong scattering, the dependence becomes nonlinear. Our model is able to accurately predict this nonlinearity and can be applied to extend the OCT studies of biological tissue towards determination of optical properties in the future.